Transboundary conservation : a new vision for protected areas (CEMEX Mexico CityMX, 2005)
Highlights the new approach of transboundary conservation - on that promises to have a profund impact on protected areas planning and biodiversity protection, and the potential to influence social and political change around the world.
Keywords: ENVIRONMENTAL PROTECTION